1991
DOI: 10.1080/15287399109531496
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana components suppress induction and cytolytic function of murine cytotoxic T cells in vitro and in vivo

Abstract: Killer lymphocytes play a major role in host defense against tumors and infectious diseases. Previously, we reported that delta-9-tetrahydrocannabinol (THC) and II-hydroxy-delta-9-tetrahydrocannabinol (II-hydroxy-THC) suppressed the cytolytic activity of cultured natural killer (NK) cells. Also, we showed that the drugs appeared to be affecting a stage in the killing process subsequent to the binding of the killer cell to the target cell. In the present report, we have extended these studies to an examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…While the immunosuppressive effects of cannabinoids (Cabral and Vasquez, 1992;Morahan et al, 1979) and their modulatory activities on immune cell functions (Cabral and Mishkin, 1989;Fischer-Stenger et al, 1992;Klein et al, 1991) have been reported previously, there is recent evidence supporting the premise that cannabinoids also have anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998), and anti-tumor properties (GalveRoperh et al, 2000). Cannabinoids have been shown to be neuroprotective in a variety of in vitro and in vivo models of neuronal excitotoxicity (van der Stelt and Di Marzo, 2005;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…While the immunosuppressive effects of cannabinoids (Cabral and Vasquez, 1992;Morahan et al, 1979) and their modulatory activities on immune cell functions (Cabral and Mishkin, 1989;Fischer-Stenger et al, 1992;Klein et al, 1991) have been reported previously, there is recent evidence supporting the premise that cannabinoids also have anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998), and anti-tumor properties (GalveRoperh et al, 2000). Cannabinoids have been shown to be neuroprotective in a variety of in vitro and in vivo models of neuronal excitotoxicity (van der Stelt and Di Marzo, 2005;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…6). A nonexhaustive list of in vitro effects includes inhibition of the proliferative responses of T lymphocytes (7), inhibition of cytotoxic T cell activity (8), suppression of macrophage function and antigen presentation (9,10), and inhibition of NO production by macrophages (11). Reports on the in vitro effects of CBD on immune cells are scarce and include the modulation of tumor necrosis factor (TNF), IL-1, and IFN-␥ by human peripheral blood mononuclear cells (12,13) and the suppression of chemokine production by a human B cell line (14).…”
Section: Annabidiol (Cbd) Is One Of the Major Components Ofmentioning
confidence: 99%
“…However, a variety of suppressive and inhibitory effects on the immune response induced by A-9-tetrahydrocannabinol (A9-THC), which is the major psychoactive component of marijuana, has been described both in vivo and in vitro (Baczynsky and Zimmerman, 1983;Titishov et al, 1989). The immunosuppressive effects of d9-THC include the inhibition of mitogen-induced T lymphocyte proliferation (Pross et al, 1987;Luo et al, 1992), the inhibition of y-interferon production (Blanchard et al, 1986) and the suppression of induction and cytolytic function of cytotoxic T cells (Klein et al, 1991). As A9-THC has proved unsatisfactory as a probe for the cannabinoid receptor due to non-specific binding to everything including cell membranes (Marx, 1990), the possibility that A9-THC might yield its effects simply by perturbing cell membranes and thereby altering cellular functions has been raised (Tahir and Zimmerman, 1991 ;Watzl et al, 1991).…”
mentioning
confidence: 99%